Case report: Cilioretinal artery occlusion combined with central retinal vein occlusion as the initial presentation of pulmonary arterial hypertension - Gao, Yane; Xie, Xiaofeng; Li, Jiao; Mu, Qingshuai; Wang, Xingrong; Wang, Shuya (Frontiers in Medicine, 2024)
BackgroundPulmonary arterial hypertension (PAH) is characterized by elevated pulmonary artery pressure and vascular resistance, leading to systemic venous hypertension and potential right heart failure. These elevated pressures can extend to ocular veins, resulting in complications such as central retinal vein occlusion (CRVO). This case report highlights a rare instance of CRVO combined with cilioretinal artery occlusion (CilRAO), an uncommon ocular manifestation associated with PAH.Case presentationA 13-year-old girl with a history of surgically repaired ventricular septal defect presented with sudden vision loss and a central visual field defect. Investigation confirmed CRVO and an unusual concurrent CilRAO. Although laboratory tests were inconclusive, the echocardiographic examination suggested severe pulmonary arterial hypertension (PAH). The patient received treatment with Bosentan and traditional Chinese medicine, which improved her vision to 20/20, though a paracentral scotoma remained.ConclusionThis case underscores the critical link between systemic cardiovascular abnormalities and ocular health in PAH, where elevated venous pressure can result in severe and distinctive ocular manifestations. The co-occurrence of CRVO and CilRAO in this patient highlights the susceptibility of cilioretinal arteries to hemodynamic changes, as these arteries lack autoregulatory capacity. Additionally, this case demonstrates the potential for positive outcomes in ocular lesions with targeted PAH therapy. Importantly, it emphasizes the need for vigilance when managing complex cases where conclusions cannot be drawn solely from ocular findings. A multidisciplinary approach and comprehensive diagnostics are essential for identifying underlying causes, ensuring active treatment, and preventing permanent vision loss and serious systemic complications.